Найдите корень уравнения -0,9×(х-4)-3,3=0,6×(2-х)

mariooouvanov mariooouvanov    1   22.09.2019 21:20    0

Ответы
айсу20 айсу20  08.10.2020 10:37
0,9x +3,6-3,3=1,2-0,6x                                                                                                       3,6-3,3-1,2=-0,6x+0,9x                                                                                                      -0,9=0,3x                                                                                                                            x=-0,9/0,3                                                                                                                             x=-3                           
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика